1994
DOI: 10.1016/0270-9139(94)90876-1
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of collagen α1(I) gene expression is associated with lipid peroxidation in hepatocellular injury: A link to tissue fibrosis?,

Abstract: We have shown that lipid peroxidation stimulates collagen alpha 1(I) gene transcription in cultured cells. Because increased lipid peroxidation and collagen production coexist in many hepatic disorders, including experimental carbon tetrachloride intoxication, we investigated whether lipid peroxidation modulates collagen gene expression in rats treated with carbon tetrachloride. In this animal model, we show colocalization of increased collagen alpha 1(I) mRNA with lipid peroxidation by means of in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
99
1
6

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 0 publications
11
99
1
6
Order By: Relevance
“…7 In this study, all patients were regularly supplemented with vitamin A and those with severe fibrosis or cirrhosis at biopsy had serum levels of retinol similar to those in matched control patients with CF without liver disease (data not shown). Lipid peroxidation might influence the development of liver disease, [42][43][44] but the patients with severe fibrosis or cirrhosis had serum levels of ␣-tocopherol within the normal reference interval and did not differ from patients with CF without liver disease (data not shown). Similar to other studies, we found no correlation among liver disease and lung function or bacterial colonization, implying that bacterial toxin production had no great impact on liver damage.…”
Section: Discussionmentioning
confidence: 93%
“…7 In this study, all patients were regularly supplemented with vitamin A and those with severe fibrosis or cirrhosis at biopsy had serum levels of retinol similar to those in matched control patients with CF without liver disease (data not shown). Lipid peroxidation might influence the development of liver disease, [42][43][44] but the patients with severe fibrosis or cirrhosis had serum levels of ␣-tocopherol within the normal reference interval and did not differ from patients with CF without liver disease (data not shown). Similar to other studies, we found no correlation among liver disease and lung function or bacterial colonization, implying that bacterial toxin production had no great impact on liver damage.…”
Section: Discussionmentioning
confidence: 93%
“…2,[33][34][35] Moreover, some of these aldehydes, including malondialdehyde and 4-hydroxy-2,3-nonenal, are also fibrogenic and enhance the production of type I collagen. [7][8][9] Recently, it has been shown that when rat liver epithelial cells are treated with 4-hydroxy-2,3-nonenal, there is induction of an oxidative stress state manifested by a significant increase in intracellular peroxides. 36 Moreover, in cultured human HSC, 4-hydroxy-2,3-nonenal directly interacts with the p46 and p54 isoforms of the c-Jun terminal kinase and these protein adducts are translocated to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] It has been already shown that there is a direct connection between lipoperoxidation and fibrogenesis. 7 Moreover, aldehydes generated during lipoperoxidation, such as malondialdehyde and 4-hydroxy-2,3-nonenal, also induce the expression of type I collagen in cultured hepatic stellate cells (HSC). 8,9 When ethanol is metabolized via alcohol dehydrogenase, its metabolite acetaldehyde is fibrogenic and induces the expression of type I collagen when added to cultured HSC, but not to hepatocytes.…”
mentioning
confidence: 99%
“…Insulin-resistant states are characterised by oxidative modification of circulating LDL cholesterol particles, which are responsible, among other factors, for damage to the vascular endothelium [17]. Oxidative stress has been involved in the development of steatosis and its progression to steatohepatitis [18,19]. Based on these findings, we investigated the oxidative status of circulating lipids in NAFLD by measuring the in vitro susceptibility of serum LDL to oxidative damage.…”
Section: Introductionmentioning
confidence: 99%